'Fine-Tuning the Marine Corps' Counterinsurgency Capabilities - Ruvalcaba, Jaime (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. No abstract available.